The stonekeeper's curse - Kibuishi, Kazu 1978- (New York Graphix, an imprint of Scholastic, 2009)
Emily and her brother Navin head for Kanalis to find an antidote for the poison that is killing their mother
2
Keywords: Amulets -- Comic books, strips, etc; Amulets -- Juvenile fiction; Brothers and sisters -- Comic books, strips, etc; Brothers and sisters -- Juvenile fiction; Haunted houses -- Comic books, strips, etc; Haunted houses -- Juvenile fiction; Magic -- Comic books, strips, etc; Magic -- Juvenile fiction; Amulets -- Fiction; Brothers and sisters -- Fiction; Haunted houses; Magic -- Fiction; Graphic novels; Proofs (Printing); Cartoons and comics; Fantasy; Graphic novels